Laser processing of Al2O3/a‐SiCx:H stacks: a feasible solution for the rear surface of high‐efficiency p‐type c‐Si solar cells. (26th April 2012) - Martín, I.; Ortega, P.; Colina, M.; Orpella, A.; López, G.; Alcubilla, R.
Abstract We explore the potential of laser processing aluminium oxide (Al2O3)/amorphous silicon carbide (a‐SiCx:H) stacks to be used at the rear surface of p‐type crystalline silicon (c‐Si) solar cells. For this stack, excellent quality surface passivation is measured with effective surface recombination velocities as low as 2 cm/s. By means of an infrared laser, the dielectric film is locally opened. Simultaneously, part of the aluminium in the Al2O3 film is introduced into the c‐Si, creating p+ regions that allow ohmic contacts with low‐surface recombination velocities. At optimum pitch, high‐efficiency solar cells are achievable for substrates of 0.5–2.5 Ω cm. Copyright © 2012 John Wiley & Sons, Ltd.